Current research toward optimizing dosing of first-line antituberculosis treatment - McIlleron, Helen (Expert Rev Anti Infect Ther, 2018)
Introduction: Drug concentrations in tuberculosis patients on standard regimens vary widely with clinically important consequences. Areas covered: We review the available literature identifying factors correlated with pharmacokinetic variability of antituberculosis drugs. Based on population pharmacokinetic models and the weight, height, and sex distributions in a large data base of African tuberculosis patients, we propose simplified weight-based doses of the available fixed dose combination(FDC) for adults with drug susceptible tuberculosis. Emerging studies will support optimized weight-based dosing for children. Other sources of important pharmacokinetic variability include genetic variants, drug-drug interactions, formulation quality, and methods of preparation and administration. Expert commentary: Optimized weight band-based dosing will result in more equitable distribution of drug exposures by weight. The use of high doses of isoniazid in patients with drug-resistant tuberculosis would be safer and more effective if a feasible test was developed to allow stratified dosing according to acetylator type. There is an urgent need for more suitable formulations of many second-line drugs for children. The adoption of new technologies and efficient FDC design may allow further advances for patients and treatment programs. Lastly, current efforts to ensure adequate quality of antituberculosis drug products are not preventing the use of substandard products to treat patients with tuberculosis.